2022
DOI: 10.1123/ijspp.2022-0091
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Physical Factors of Tennis Serve Velocity: A Brief Review

Abstract: Purpose: To review the main physical aspects that could positively or negatively influence serve velocity (SV). Methods: An examination of existing literature including studies analyzing positive (biomechanical aspects, anthropometrics, range of motion, strength, and power) and negative (competition-induced fatigue) associations to SV are summarized in this review. Results: Aspects such as lower-leg drive, hip and trunk rotations, upper-arm extension, and internal rotation seem to be the major contributors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Consequently, these measures provide information for the interpretation of other characteristics [ 48 , 49 , 51 , 55 , 57 ]. To illustrate, strong evidence was found that body height is related to serve speed in tennis [ 41 , 66 69 ], while other studies found that serve speed was related to overall performance in tennis [ 32 , 33 , 42 ]. Together, this example shows how anthropometrics may be indirectly related to performance.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these measures provide information for the interpretation of other characteristics [ 48 , 49 , 51 , 55 , 57 ]. To illustrate, strong evidence was found that body height is related to serve speed in tennis [ 41 , 66 69 ], while other studies found that serve speed was related to overall performance in tennis [ 32 , 33 , 42 ]. Together, this example shows how anthropometrics may be indirectly related to performance.…”
Section: Discussionmentioning
confidence: 99%
“…This paper takes the mixed Gaussian group composed of Q Gaussian components as the research starting point. 5 The method is a mathematical expression for the probability assignment of time pixels. The probability of α j for a pixel at time t is expressed as:…”
Section: Prediction Of the Best Hitting Point For A Tennis Servementioning
confidence: 99%
“…Such a slouched posture angle is associated with decreased range of motion in glenohumeral external rotation (20,21) and arm abduction (20,22), decreased glenohumeral external rotator muscle strength, and decreased scapular posterior tilt (20,23). Like positive correlations have been reported between tennis serve velocity and glenohumeral range of motion and strength (24), preventing the consequences of deficiencies in trunk extension and acquired slouched posture on shoulder functions involved to achieve tennis stroke may be a goal of prevention program for tennis players.…”
Section: Introductionmentioning
confidence: 96%